ANALISIS PERKEMBANGAN SOSIAL EMOSIONAL SISWA BERKEBUTUHAN KHUSUS DI SD SONOSEWU KABUPATEN BANTUL - Cipta Saputra, Rendika; Rian Nurizka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of inclusive education and the socio-emotional development of students with special needs (ABK) at Sonosewu Elementary School, Bantul Regency. Inclusive education is essential as it provides equal learning opportunities while supporting students’ social and emotional skills in a regular school environment. The research used a descriptive qualitative approach with data collected through observation, interviews with the principal, teachers, and students, as well as documentation. Data were analyzed through reduction, presentation, and conclusion drawing, while validity was ensured using triangulation. The findings show that the inclusive program at Sonosewu Elementary School has been implemented since 2020. The school provides disability-friendly facilities, adjusted learning resources, counseling services, and individualized learning strategies. Teachers play a central role in adapting methods, conducting assessments, and offering assistance, while parental involvement through regular meetings also supports the program’s success. In terms of socio-emotional development, students with special needs show progress in peer interaction, communication, emotional regulation, and self-confidence. However, challenges remain, such as the limited number of special assistant teachers, unequal facilities, and the diverse needs of students. Overall, inclusive education at Sonosewu Elementary School has a positive impact on the socio-emotional development of students with special needs and may serve as a reference for other schools to build inclusive and sustainable learning environments.Keywords: Inclusive Education, Socio-Emotional, Students With Special Needs